A Highly Efficient Heterogeneous Catalyst of Bimetal-Organic Frameworks for the Epoxidation of Olefin with H2O2 - Wang, Fei; Meng, Xiang-Guang; Wu, Yan-Yan; Huang, Hong; Lv, Jing; Yu, Wen-Wang (Molecules (Basel, Switzerland), 2020)
A series of bimetel organic framework MnxCu1−x-MOF were prepared. The MOFs was characterized and analyzed by powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The catalytic activity of the developed catalyst was tested on various olefins by H2O2 as oxidant. The MOFs catalyst exhibits excellent catalytic activity for the epoxidations of various aromatic and cyclic olefins. Particularly, Mn0.1Cu0.9-MOF can achieve 90.2% conversion of styrene with 94.3% selectivity of styrene oxide at 0 °C after reaction 6 h. The MOF exhibited the catalytic activity of inverse temperature effect on epoxidation of styrene. The introduction of copper component can stabilize H2O2 and inhibit its decomposition to a certain extent. The catalyst can be reused at least five cycles without significant loss in activity towards epoxidation.